2008
DOI: 10.1111/j.1745-459x.2007.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire Practice: What Happens When the Jar Scale Is Placed Between Two “Overall” Acceptance Scales?

Abstract: Using the observational analysis of two different foods as test products, this note examined some interesting findings that emerge when the just-aboutright (JAR PRACTICAL APPLICATIONSThe results of the present analysis suggest that overall acceptance/liking can be the last question in the questionnaire design. That location is very important for the sensory analysis of foods eaten over time and then rated, as well as personal care and cosmetic studies where the products are used over 4 Corresponding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Below JAR point deviations (d) and above JAR point deviations (s). different formulations using the just about right (JAR) scales (Gacula et al, 2008). Relationship between consumer perceptions and the overall acceptability of formulations can inform about in what extent the sensory differences perceived among samples by consumers influences their acceptability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Below JAR point deviations (d) and above JAR point deviations (s). different formulations using the just about right (JAR) scales (Gacula et al, 2008). Relationship between consumer perceptions and the overall acceptability of formulations can inform about in what extent the sensory differences perceived among samples by consumers influences their acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…When conducting this type of study, one must take into account that there is no cause-effect connection between the independent factors (ingredients) controlled by the experimenter and the dependant factor (acceptability), and it is necessary to analyse to what extent could a possible interaction between the ingredients cause perceptible variations of the sensory features and if any such variations affect the acceptability. The just about right scales can play a diagnostic role to determine how the consumer feels the product (Gacula, Mohan, Faller, Pollack, & Moskowitz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The use of JAR scales for product optimization has been questioned by some authors who do not consider it as effective as other methods (Epler et al 1998). Other authors indicate that JAR scales can be used with the hedonic scale in consumer testing to provide directional information for food optimization (Gacula et al 2008;Xiong and Meullenet 2006). Recently, Lovely and Meullenet (2009) compared four approaches to optimize acceptance of strawberry yogurt and observed that the JAR scales were an acceptable alternative to more complicated methodologies based on different deterministic and probabilistic preference mapping approaches.…”
Section: To What Extent Does the Variation In Perceived Sensory Charamentioning
confidence: 97%
“…However, JAR scales are not appropriate to study the psychophysical (stimuli-sensory response) or psychohedonic (sensory response-liking) functions. Despite their practical validity, the main drawbacks of JAR scales are related with the interpretation and analysis of the JAR data and how these data relate to hedonics (Gacula et al 2007(Gacula et al , 2008Xiong and Meullenet 2006).…”
Section: To What Extent Does the Variation In Perceived Sensory Charamentioning
confidence: 99%
“…The Just About Right scales can play a diagnostic role to determine how the consumer feels the product (Gacula, Mohan, Faller, Pollack, & Moskowitz, 2008).…”
Section: Introductionmentioning
confidence: 99%